Automatic detection of microcracks on the surface of special steel wire based on remanence effect. Issue 2 (4th March 2023) - Jiang, Yutong; Yu, Runqiao; Xiong, Lechao; Chen, Tao; Yao, Hui
ABSTRACT: In this study, a remanence detection technology and double-layer sensor crack depth quantitative method for the on-line detection of microcracks on the surface of steel wire using remanence were developed. First, an instrument and a verification experiment were designed. Second, the magnetic signal of the prefabricated crack was analysed, and a defect recognition algorithm was designed. Finally, a detection instrument was applied in the industrial field. The results indicate that the practical application of remanence detection technology is feasible, the recognition algorithm is accurate and reliable, and a minimum crack depth of 0.078 mm can be detected. The magnetic anomaly amplitude difference of the double-layer sensor is positively correlated with the crack depth. The maximum error rate of the quantitative formula for the depth obtained by the fitting method is 10.95%. However, distinguishing the tilt direction of the crack from the shape of the notch remains a challenge for remanence detection technology.